A New Fragment for Nicolaus of Damascus? A Note on Suda α 1272 - Paradiso, Annalisa (Histos, 2015)
This paper deals with Suda α 1272, providing its source, namely Nicolaus of Damascus, abridged by the Constantinian compilers and possibly depending on Xanthus of Lydia.